Lorenz Curve Application in Oil-Gas Industry Economy - Salimova, S.G. (Herald of Azerbaijan Engineering Academy, 2023)
A methodic approach to the Lorenz curve application in the efficiency analysis of the Oil-Gas Production Department (OGPD) main production well stocks usage is developed. The scientific-research work consists of two stages: preliminary and main. In the preliminary stage, gathering and systematization of major technical-economic, accounting, geological and other indexes are conducted, the basic chart for the OGPD well survey is developed. In main stage, considering well division by quintile, the following action are carried out: 1) the factorial application of the Lorenz curve (calculation); 2) calculation of return on assets by all wells, as well as necessary calculations on determinant factors influencing return on assets. They are followed by the Lorenz curve plotting on determinant factors. Then, based on well division by quintile, the graphs on return of assets and determinant factors are developed.